ISOLATION AND INCIDENCE OF THERMOPHILIC FUNGI FROM VARIOUS THERMOGENIC HABITATS IN ANDHRA PRADESH - S.SANTOSH KUMAR AND; EDLA SUJATHA (International Journal of Pharma and Bio Sciences, 2013)
A total of 400 samples were collected from different thermogenic habitats such as nests of birds, decomposing litter, soils from furnace area, cattle dung, zoo dump, industrial waste, vegetable market compost, mushroom compost, horse dung, municipal waste, chicken manure and coal mine soils of Godavari Khani (Karimnagar) and Bhoopalpally (Warangal) group of mines in Andhra Pradesh. From which 40 isolates including 10species of 10genera were isolated. Among the thermophilic fungi Rhizomucor pusillus and Humicola insolens present nearly in all substrates. A novel strain Sordariales sp.A.P-2012 strain was isolated from nest material and an uncultured compost fungus was isolated from the cattle dung. Scytalidium thermophilum strain B1 was successfully isolated from mushroom compost and Sporotrichum thermophile from decomposed litter are adapted to grow at a temperature maximum of 65°C and 60°C respectively.